Recovery of Post Thyroidectomy Aphonia with Peri Recurrent Laryngeal Nerve Injection of Meloxicam - Battista Borghi; Aladdin Safi; Claudio Santangelo; Raffaele Borghi (Global Journal of Anesthesiology - Peertechz Publications, 2015)
Objectives: The aim of this study was to assess the effect of perineural injection of meloxicam on the recovery of vocal cord paresis due to recurrent nerve injury after thyroid surgery. A secondary objective was listed the neural inflammation as possible risk factor for delayed recovery of vocal cord paresis. Methods: 47 years old female, two months after thyroid surgery still complaining of aphonia and dyspnea, due to vocal cord paresis bilaterally, bilaterally injection with 7.5mg of meloxicam was done for peri neural recurrent laryngeal nerve aiming to assess the effect of meloxicam on functional recovery of vocal cord. Results: A significant improvement in the basic function of vocal cord was noticed immediately after perineural injection of meloxicam bilaterally for recurrent laryngeal nerves injury post thyroidectomy. Conclusions: Perineural injection of meloxicam appears to be a noval and potentially promising therapeutic option for patients with vocal cord paresis due to transient recurrent laryngeal nerve injury. Further clinical studies are necessary to determine the optimal use of this approach for treatment for both acute and chronic bases. Neural inflammation of recurrent laryngeal nerve could be possible cause of vocal cord paresis and delayed functional recovery.